Jaws - Benchley, Peter (New York : Bantam Books, 1974)
It's out there in the water--waiting. Nature's most fearsome predator. It fears nothing. It attacks anything. It devours everything. And the seaside community of Amity is at its mercy.
Keywords: jaws